The Social Model of Translation and Its Application to Internet Search Engines Specialized in Health: The ASEM Search Engine for Neuromuscular Diseases - Miquel-Vergés, Joan; Sánchez-Trigo, Elena (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
The use of the Internet as a source of health information is greatly increasing. However, identifying relevant and valid information can be problematic. This paper firstly analyses the efficiency of Internet search engines specialized in health in order to then determine the quality of the online information related to a specific medical subdomain like that of neuromuscular diseases. Our aim is to present a model for the development and use of a bilingual electronic corpus (MYOCOR), related to the said neuromuscular diseases in order to: a) on one hand, provide a quality health information tool for health professionals, patients and relatives, as well as for translators and writers of specialized texts, and software developers, and b) on the other hand, use the same as a base for the implementation of a search engine (using keywords and semantics), like the ASEM (Federación Española Contra las Enfermedades Neuromusculares) search engine for neuromuscular diseases.